Physiological and Evolutionary Changes in a Biological Control Agent During Prey Shifts Over Several Generations - Chen, Mei-Lan; Wang, Tao; Huang, Yu-Hao; Qiu, Bo-Yuan; Li, Hao-Sen; Pang, Hong (Frontiers in Physiology, 2018)
Biological control agents usually suffer from a shortage of target prey or hosts in their post-release stage. Some predatory agents turn to attacking other prey organisms, which may induce physiological and evolutionary changes. In this study, we investigated life history traits, gene expression and genotype frequency in the predatory ladybird beetle Cryptolaemus montrouzieri during experimental prey shifts. C. montrouzieri were either continuously fed on aphids Megoura japonica as an alternative prey for four generations or were shifted back to the initial prey mealybugs Planococcus citri in each generation. In general, the utilization of aphids resulted in reduced performance and severe physiological adjustments, indicated by significant changes in development and fecundity traits and a large number of differentially expressed genes between the two offering setup prey treatments. Within the aphid-fed lines, performance regarding the developmental time, the adult weight and the survival rate recovered to some level in subsequent generations, possibly as a result of adaptive evolution. In particular, we found that a shift back to mealybugs caused a gradual increase in fecundity. Accordingly, a genotype of the fecundity-related gene vitellogenin, of which there were several minor alleles in the initial population, became the main genotype within four generations. The present study explored the short-term experimental evolution of a so-call specialist predator under prey shift conditions. This potential rapid adaptation of biological control agents to novel prey will increase environmental risks associated with non-target effects.